2016
DOI: 10.1590/0001-3765201620150282
|View full text |Cite
|
Sign up to set email alerts
|

Sandy beaches: state of the art of nematode ecology

Abstract: In this review, we summarize existing knowledge of the ecology of sandy-beach nematodes, in relation to spatial distribution, food webs, pollution and climate change. We attempt to discuss spatial scale patterns (macro-, meso-and microscale) according to their degree of importance in structuring sandy-beach nematode assemblages. This review will provide a substantial background on current knowledge of sandybeach nematodes, and can be used as a starting point to delineate further investigations in this field. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Overall, meiofaunal assemblage at Gramuté beach was mainly dominated by Crustacea and Annelida (46% and 28% of reads), with Nematoda representing only 12% of the meiofauna over the year. Nematodes often dominate meiofauna in benthic habitats, with high diversity in the full range of beach types ( Maria et al, 2016 ), for example representing 50–90% of the total individuals in medium to fine sandy sediments ( Coull, 1988 ; Giere, 2009 ; Merckx et al, 2009 ) but also showing high diversity in coarse sand beaches ( Gheskiere et al, 2005 ). However, crustaceans and nematodes become more representative during the winter (57% and 17% of sequence reads), while annelids are less (11% of sequence reads).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, meiofaunal assemblage at Gramuté beach was mainly dominated by Crustacea and Annelida (46% and 28% of reads), with Nematoda representing only 12% of the meiofauna over the year. Nematodes often dominate meiofauna in benthic habitats, with high diversity in the full range of beach types ( Maria et al, 2016 ), for example representing 50–90% of the total individuals in medium to fine sandy sediments ( Coull, 1988 ; Giere, 2009 ; Merckx et al, 2009 ) but also showing high diversity in coarse sand beaches ( Gheskiere et al, 2005 ). However, crustaceans and nematodes become more representative during the winter (57% and 17% of sequence reads), while annelids are less (11% of sequence reads).…”
Section: Discussionmentioning
confidence: 99%
“…Although the roles of beach meiofauna in recycling nutrients and influencing beach bacterial populations have not been quantified extensively and examined under a range of conditions, several studies have demonstrated that meiofauna are a functionally important beach community component [ 19 ] and provide useful information for policy makers [ 68 ]. Unfortunately, changes to the physical environment of the beach, arising from anthropogenic activities [ 58 , 69 72 ] and responses to shoreline erosion, may be altering beach meiofaunal communities in ways that affect beach processes, before we fully understand those processes.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature, salinity, light, gravity and oxygen tension gradients are known to play an essential role in conditioning the spatial distribution of intertidal species on sandy beaches (Jansson 1968a, Giere 2009, Maria et al 2016. Therefore, the aim of the present study was to test the effect of these factors on the survival and vertical distribution of P. eschaturus in laboratory conditions.…”
Section: Introductionmentioning
confidence: 97%